The Impact of Flood on Water Quality In Muar River Along Jalan Panchor, Muar, Johor - Muhammad Akmal Mohd Nizam,; Rosli, Mohd Arif (Progress in Engineering Application and Technology, 2024)
This research explores the complex relationship between flood occurrences and riverwater quality, highlighting the significant hazards they pose to river ecosystems. It useshydrological, ecological, and environmental science perspectives to understand thelong-term effects of floods on aquatic ecosystems and communities reliant on thesewater sources. The study's goal is to provide an enhanced awareness of the complexrelationships that exist between floods and river water quality by determined the postfloodsituation of Muar River along Jalan Panchor, Johor water quality parameter andcategorise it in accordance with the Malaysian Water Quality Index (WQI) to representclean, slightly polluted, and polluted then compared to the pre-flood. Water samplewas taken for five stations along Panchor River'. In order to identify the initialcharacteristics of the water and the Water Quality Index (WQI), it was analysed usingthe WQI parameter such as Biochemical Oxygen Demand (BOD5), Chemical OxygenDemand (COD), Total Suspended Solids (TSS), Ammoniacal Nitrogen (AN), and pHscale. Conducting an experiment allowed for the thorough assessment andclassification of the water quality, which were then compared to the DOE criteria forMuar River. Results show that overall water quality of Muar River along Jalan Panchorcan be classified as Slightly Polluted or Class III, with WQI values ranging from 51.9to 76.5. However, on the impact of the flood to the water quality to the river shows anincreased in WQI with 65.01 for pre-flood to 68.51 for post flood. It can be concludedthat which indicate a better water quality index after the flood. This could be due tothe good water circulation, dilution, and mixing.